Changing Interactions Between Physician Trainees and the Pharmaceutical Industry: A National Survey - Austad, Kirsten E. (Springer US, 2013)
BACKGROUND: Increasingly, medical school policies limit pharmaceutical representatives’ access to students and gifts from drugmakers, but little is known about how these policies affect student attitudes toward industry. OBJECTIVE: To assess interactions between trainees and the pharmaceutical industry, and to determine whether learning environment characteristics influence students’ practices and attitudes. DESIGN, PARTICIPANTS: We conducted a cross-sectional survey with a nationally-representative sample of first- and fourth-year medical students and third-year residents, stratified by medical school, including ≥ 14 randomly selected trainees at each level per school. MAIN MEASURES: We measured frequency of industry interactions and attitudes regarding how such interactions affect medical training and the profession. Chi-squared tests assessed bivariate linear trend, and hierarchical logistic regression models were fitted to assess associations between trainees’ attitudes and their schools’ National Institutes of Health (NIH) funding levels and American Medical Student Association (AMSA) PharmFree Scorecard grades reflecting industry-related conflict of interest policies. KEY RESULTS: Among 1,610 student (49.3 % response rate) and 739 resident (43.1 %) respondents, industry-sponsored gifts were common, rising from 33.0 % (first-year students) to 56.8 % (fourth-year students) and 54 % (residents) (p < 0.001). These gifts included meals outside the hospital (reported by 5 % first-year students, 13.4 % fourth-year students, 27.5 % residents (p < 0.001)) and free drug samples (reported by 7.4 % first-year students, 14.1 % fourth-year students, 14.3 % residents (p < 0.001)). The perception that industry interactions lead to bias was prevalent, but the belief that physicians receive valuable education through these interactions increased (64.1 % to 67.5 % to 79.8 %, p < 0.001). Students in schools receiving more NIH funding reported industry gifts less often (OR = 0.51, 95 % CI: 0.38–0.68, p < 0.001), but the strength of institutional conflict of interest policies was not associated with this variable. CONCLUSIONS: Despite recent policy changes, a substantial number of trainees continue to receive gifts from pharmaceutical representatives. We found no relation between these outcomes and a school’s policies concerning interactions with industry. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-013-2361-0) contains supplementary material, which is available to authorized users.